Respiratory syncytial virus (RSV) antibody and small-molecule drugs: current status of clinical translation and challenges - Liu, Hanxiang; Zhong, Hui; Liu, Hanmin (Frontiers in Microbiology, 2026)
Backgroundrespiratory syncytial virus (RSV) remains a leading cause of lower respiratory tract infections worldwide, imposing a substantial disease burden on infants, older adults, and immunocompromised individuals. Despite its prevalence, therapeutic options have historically been limited, with no specific antiviral drugs widely approved for treatment until recently. The landscape is now shifting rapidly with the development of novel preventive and therapeutic agents.Contentthis review comprehensively summarizes the current status of RSV monoclonal antibodies and small-molecule antivirals, integrating mechanistic insights with clinical translational perspectives. We analyze the evolution of immunoprophylaxis from palivizumab to next-generation long-acting antibodies like nirsevimab, which have reshaped prevention strategies. Furthermore, we evaluate small-molecule agents, contrasting the limitations of early fusion inhibitors with the improved efficacy and resistance barriers of emerging polymerase inhibitors such as ziresovir.Key issuesclinical translation faces multifaceted challenges beyond molecular discovery. Major hurdles include the complexity of clinical trial designs for vulnerable populations (neonates and the elderly), the lack of globally harmonized clinical efficacy endpoints, and the risks associated with viral escape mutations. Additionally, divergent regulatory frameworks and requirements across different regions complicate the global development and registration of new RSV products.Outlookfuture advancements will likely depend on integrating emerging technologies, including mRNA platforms, gene editing, and AI-driven drug discovery. Moving forward, the field must prioritize multi-target combination therapies to mitigate resistance and establish global surveillance networks. Ultimately, international collaboration is essential to ensure equitable access, sustainable pricing, and the successful implementation of next-generation RSV therapeutics.